Sociodemographic and clinical profile of children with congenital heart disease assisted at a hospital institution - Mirna Albuquerque Frota; Ivna Silva Andrade; Zélia Maria Sousa Araújo Santos; Carlos Antônio Bruno da Silva; Ana Fátima Carvalho Fernandes (Universidade de Fortaleza, 2014)
Objective: To characterize the sociodemographic and clinical profile of children with congenital heart disease assisted at a hospital institution. Methods: A descriptive, crosssectional study conducted in the pediatric cardiology outpatient clinic of a hospital in Fortaleza, CE, Brazil, in the period from March to August 2012. It comprised a nonrandom convenience sample of 80 parents of children with heart disease aged 5 to 12 years. Information was obtained from primary data of medical records and through questionnaires covering the parent's sociodemographic characteristics, family data and the children's clinical aspects. Results: Regarding socioeconomic data, 77 (96.2%) caregivers were female, 50 (62.5%) were married or in a stable relationship, 39 (48.7%) had 10-12 years of formal education, and 69 (82.6%) reported a household income between 1 and 2 minimum wages. In the sample of children studied, 43 (53.8%) were female. The median age of the children was 8.4 years, ranging from 5-13 years. As to the age at the heart disease diagnosis, 44 (55%) occurred under the age of 6 months, regardless of the type of cardiopathy. It was detected that 19 (23.75%) were related to the disease. Conclusion: Children's caregivers were predominantly their mothers, with low income and satisfactory schooling. Early diagnosis was predominant, mainly among the children with cyanotic cardiopathy. doi:10.5020/18061230.2014.p239